Activity Test of Facial Wash Formulation Containing Ethanol Extract of Patikala Fruit (Etlingera elatior) Against the Growth of Propionibacterium acnes - Muthmainnah Thalib; Istianah Purnamasari; Nirwana Nirwana (Lembaga Pengembangan Kinerja Dosen, 2025)
Acne (acne vulgaris) in Indonesia, as a country with a tropical climate, has a high prevalence of the disease. This is caused by tropical climate conditions that support the growth of bacteria, parasites, and fungi. Propionibacterium acnes is another organism involved in skin pathogenesis. One of the plants that has antibacterial properties is the patikala fruit (Etlangiera elatior) as an anti-acne agent so it can be formulated as a facial wash preparation because it has antioxidant and antimicrobial activity. This study aims to determine whether the ethanol extract of the patikala fruit (Etlangiera elatior) can be formulated into a facial wash preparation that has good physical stability and has antibacterial activity at concentrations of 3%, 6% and 9%. This research method is a laboratory experiment that aims to formulate a facial wash preparation based on the ethanol extract of the patikala fruit (Etlangiera elatior) and test its antibacterial activity against the bacteria that causes acne, namely Propionibacterium acnes. The most effective facial wash preparation of ethanol extract of patikala fruit (Etlingera elatior) in inhibiting the growth of Propionibacterium acnes bacteria is a concentration of 9% with an inhibitory power of 16.43 mm, which is included in the strong category.